2017
DOI: 10.4103/ijem.ijem_79_17
|View full text |Cite
|
Sign up to set email alerts
|

Myopathy in patients taking atorvastatin: A pilot study

Abstract: Aim:This study aims to investigate the prevalence and risk factors of statin-induced myopathy.Subjects and Methods:A total of 200 patients aged ≥ 40 years and taking atorvastatin 10 mg/day or more for at least 2 weeks were recruited in the study. A detailed history of participants and anthropometry of study participants was recorded, and features of myopathy were explained. Biochemical investigations along with thyroid stimulating hormone (TSH) and Vitamin D were done in all patients.Results:Mean age of study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 21 publications
0
4
0
1
Order By: Relevance
“…During the treatment with statin, muscle damage was frequently reported, manifested mostly by a muscle pain associated with modest or mild increase in the serum markers of muscle damage, e.g. serum creatine kinase [19][20][21]. No clinical symptoms that might have suggested statin-induced muscle damage were seen in our patients during the study and the physical exercise was very well-tolerated.…”
Section: Discussionmentioning
confidence: 63%
“…During the treatment with statin, muscle damage was frequently reported, manifested mostly by a muscle pain associated with modest or mild increase in the serum markers of muscle damage, e.g. serum creatine kinase [19][20][21]. No clinical symptoms that might have suggested statin-induced muscle damage were seen in our patients during the study and the physical exercise was very well-tolerated.…”
Section: Discussionmentioning
confidence: 63%
“…To a lower extent, in the same study, diabetes was also identified as a risk factor for rhabdomyolysis (OR 1.96, 95%CI 1.79-2.15) [ 67 ]. Manoj et al found that diabetic patients on atorvastatin had a 7.5% prevalence of myopathy [ 68 ].…”
Section: Reviewmentioning
confidence: 99%
“…Nonetheless, all the guidelines agree on ordering diagnostic tests based on myopathic symptoms experienced by the patients. Checking serum CK levels is recommended if a patient experiences muscular side effects [ 68 ]. Furthermore, the amount of CK elevation also guides therapy.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Уровень ТТГ хотя и был в среднем выше в группе пациентов, имеющих признаки миопатии (4,05 ± 7,76 и 3,13 ± 2,88 мЕд/л), одна ко не достигал статистически значимой разницы (р > 0,05). Можно предположить, что отсутствие существенных различий обусловлено малой вы боркой пациентов [27].…”
Section: нежелательные реакции при применении статиновunclassified